PENGEMBANGAN INDUSTRI KECIL DAN MENENGAH DI KOTA SEMARANG (STUDI KASUS PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA SEMARANG DI BIDANG PERINDUSTRIAN) - Intan Andriani; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Small and Medium Industries plays an important role for the economy of the Semarang city. This sector is able to address equity in the distribution of income among regions. If the Small and Medium Industries can be maximized, the city of Semarang can raise the local revenue. This study aimed to describe and analyze the performance of industrial field in Semarang, also drives the performance of Industry Department and Trade in Semarang to implementing the Development Program of Small and Medium Industries. This study uses qualitative research with descriptive methodes. The results shows that performance in implementing the Programme for Small and Medium Industry Development has not been maximized. This assessment is based on the dimensions of productivity, quality of service, responsiveness, and accountability and reponsibility. This could be happen because the Industry can not achieve 100% of the target achievement and there has been no significant increase in the number of Small and Medium Industries. Incentives can be seen from the aspect of performance factors for Human Resources and Cultural Organization. The conclusion of this study is the performance of Department of Industry and Trade in Semarang is not yet up and need to be scaled back. Suggested for Industry increasing the quantity and quality of human resources and imposed a system of reward and punishment.